Persistent Hyperinsulinemic Hypoglycemia in Iraqi Pediatric Population: A Single Tertiary Center Experience - Munib Ahmed Al-Zubaidi; Wasnaa Hadi Abdullah; Khalid Hatem Kareem (Medical Journal of Babylon)
Background: Congenital hyperinsulinism (CHI) is an inappropriate insulin secretion by the pancreatic cells. When medical therapies are ineffective, surgical treatment is required. Objective: This study aims to evaluate the clinical characteristics of CHI patients and assess the associated factors that may affect their response to treatment. Materials and Methods: This is a retrospective study including all patients diagnosed with hyperinsulinemic hypoglycemia who were registered at the Children Welfare Teaching Hospital in Baghdad, Iraq. Patients’ data were collected including birth weight, age at presentation, and consanguinity between parents. All patients had a confirmed diagnosis of hyperinsulinism after performing a critical sample. The data of these investigations were collected in addition to the type of medical treatment they received and those who had finally undergone pancreatectomy. Results: Among the 44 patients in the study, 38 (86.4%) presented in the first year of life. Of these, 22 (57.9%) were responsive to diazoxide. In addition, 13 (34.2%) of those presenting in the first year required pancreatectomy. Among the remaining six patients who presented after the first year of life, three (50%) responded to diazoxide, while two (33.3%) required pancreatectomy. Patients who did not respond to diazoxide had higher mean insulin and age at presentation with 19.58 ± 17.28 µU/ml and 9.73 ± 28.23 months, respectively. Conclusion: While genetic study remains the gold standard for the diagnosis of CHI, clinical characteristics of patients can be the only helpful way to predict further management in countries with limited resources.